The Relationship between the Psychological Status and Pain’s Level among Breast Cancer Patients in the Chemical and Radiotherapy Center in Lattakia - نظام عفاف (Latakia University Journal -Medical Sciences Series, 2022)
Globally; Breast Cancer (BC) ranks first among other women’s cancer types. Annually; one in eight women has developed this disease. It’s the most difficult experience may face a woman in her life. Because of the complex psychological disorders that associated with it, which exacerbate her general condition, and lead her to isolation and depression. Her suffering from this disease is increasing by her feeling of pain following surgical; chemical; radiological and hormonal treatments.This study aimed to assess the relationship between psychological state and pain level among BC patients in the Chemotherapy and Radiotherapy Center in Lattakia. An interview was conducted with 50 women diagnosed with this disease in the aforementioned center while receiving treatment during the period between 15/4/2019 to 22/8/2019, and the results indicated that the vast majority of the sample had a medium and low level of psychological problems associated with infection with BC, and 62% of the sample was suffering from pain to a moderate degree, and the value of the correlation between the mean of psychological problems phrases and the average intensity of pain was R = 0.87 with statistical significance P = 0.003, which indicates the existence of a statistically significant direct relationship between psychological problems and the intensity of pain in the study sample .The study recommended the need to form a psychological support team for women with BC to alleviate the psychological symptoms accompanying the disease, and to adopt non-pharmacological methods to relieve their pain, especially during treatment.